Insects compositions at different growing phases of the Sarawak indigenous eggplant, terung asam (Solanum lasiocarpum Dunal.) with the first report of a ladybug species, Henosepilachna kaszabi (Coleoptera: Coccinellidae) as major foliage pest - Muhamad Azmi Mohammed,; Ameyra Aman-Zuki,; Marthiuz Ghany Buang,; Abang Abdul Rahim Ossen,; Nurul Imani Che Pa,; Salmah Yaakop, (Penerbit Universiti Kebangsaan Malaysia, 2023)
Solanum lasiocarpum (Solanaceae), commonly known as Terung Asam, is an indigenous crop in Sarawak, Borneo. The S. lasiocarpum is a renowned crop and is significant to the local and smallholder farmers for their household income. Study of insects associated with this crop is currently limited and lacking, despite their importance for Sarawak’s agronomy. Hence, this study aimed to determine the associated insect species with S. lasiocarpum throughout the plant growth, namely, vegetative, flowering, and fruiting phases. Henosepilachna kaszabi (Coccinellidae) and mealybug Pseudococcidae were recorded as primary pests, while Anoplolepis gracilipes (Formicidae) and Polyrhachis sp. (Formicidae) as indirect pests for flowering and fruiting phases. Larvae and adults of H. kaszabi were sighted infesting leaves, stems, and roots, while Pseudococcidae congregated and infested the stems of S. lasiocarpum. Other visiting insects for S. lasiocarpum were also listed in this study. This study provides preliminary information regarding the insect pests of S. lasiocarpum for future effective pest management on this crop.